How is the Concept of Mental Peace according to the Quran in Thematic Tafsir Studies? - Rahmawati, Siti; Sholeh, Muh Ibnu; Al Ayyubi, Ibnu Imam; Nurlismaya, Shonia Kamaliya; Hayati, Ai Faridatul (Jurnal test, 2024)
This research aims to look more deeply at the concept of mental peace according to the Koran which is reviewed based on thematic interpretation studies. Mental restlessness can be caused by feelings of anxiety that accumulate it can cause serious illnesses. The method used is a qualitative method with data collection techniques carried out using observation and interviews. The data analysis techniques used include data collection, data reduction, data presentation, and conclusion. It can be concluded that peace of mind can be seen from behavior, an unhurried attitude, full of calculations and mature considerations as well as being wise, correct, and appropriate in acting. This is also found in the Al-Quran, namely in Q.S Ar-ra'du verse 28, Q.S Thaha verse 124, Q.S al-Hadid verse 16, Q.S Al-Baqarah verses 152, 198, 200-202, and the Hadith of Rasulullah Saw which holistically explains about inner appreciation to gain mental peace through spiritual methods with Dhikr such as saying or reciting tasbih, tamed, takbir, or tahlil sentences. This is preferred solely to obtain peace and tranquility of the soul amid today's dominating flow of information. This is the concept of mental peace that can be obtained based on a thematic interpretation, essentially by remembering Allah Swt through Dhikr.